Theories of Policy Accommodation : The Persistence of Inflation and Gradual Stabilizations - De Gregorio, Jose (IMF Working Papers; Working Paper, 1992)
Persistent inflation and slow stabilization are usually the result of policy accommodation resorted to in an attempt to avoid the recessionary costs of a sharp reduction of inflation. This paper reviews three explanations for why policymakers, despite their dislike of inflation, may nevertheless choose to adopt accommodative policies. It emphasizes the role of indexation, uncertainty about policymakers' preferences, and the existence of fixed costs associated with the implementation of a stabilization program. The paper also presents some evidence on the extent of persistence of inflation across countries.